The Dominant Factors of Occupational Accident Risk Potential in Jember Regency - Dhanny Indra Prasetya; Isa Maarufi; Sugeng Winarso (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2023)
The construction industry sectors have a significant risk of work accidents, making it one of the industries with a relatively high level of risk. According to the ILO, in 2018, 2,78 million workers died each year due to work accidents (13,7%) and diseases due to occupation (86,3%). This study aims to analyze the risk of work accidents among informal housing construction workers in Jember Regency. This type of research is quantitative descriptive research. The research was conducted in housing that is under construction which is located in Sumbersari District, Patrang District, and Kaliwates District, Jember Regency. The population in this study involved informal construction workers in Jember Regency. The population in this study included an unlimited population because easily entered by anyone and as the characteristics of informal construction do not require special skills. The sampling technique used non-probability sampling techniques, the sample calculation used quota sampling. The number of samples used was 97 respondents. The Accidental Sampling technique was used to select the samples. Risk analysis was through the Delphi method. Based on the calculation of all the risks that exist, it is indicated that there are three hazard risks with priority status, which means that they require immediate treatment. The risk identified was the risk of falling at the roof work stage (CPE 211,22), the risk of electric shock during the electrical installation work stage (CPE 197,85), and the use of PPE during the roof work stage (CPE 184,75). There needs to be risk control concerning the hierarchy of hazard control. Keyword: Construction, informal, work accident